Phenol methylation on acid catalysts: Study of the catalyst deactivation kinetics and mechanism - Sad, Maria Eugenia (2014)
The kinetics and mechanism of coke formation and catalyst deactivation during the synthesis of cresols from phenol methylation were investigated on SiO2–Al2O3, tungstophosphoric acid (HPA) supported on silica, and zeolites HBEA, HZSM5, HMCM22 and HY. The nature, density and strength of surface acid sites were probed by temperature programmed desorption of NH3 coupled with infrared spectra of adsorbed pyridine. Coke formed on the catalysts during reaction was characterized by temperature programmed oxidation. All the samples deactivated on stream. A linear correlation was observed between the initial catalyst deactivation and the amount of coke, thereby indicating that coke formation was responsible for the activity decay. Coking kinetic studies showed that a significant part of coke was rapidly formed from the reactants. When methanol was feeding alone, significant amounts of carbon were formed on the catalysts (between 0.6% and 6.2%C), particularly on samples containing mainly strong Brønsted acid sites. Nevertheless, the coke amounts formed during phenol methylation were clearly higher (between 3.7% and 14.9%C), which showed that phenol was also responsible for coke formation. More insight on the role of phenol and methanol on coke formation was obtained by characterizing the coke nature using infrared spectroscopy. Coked samples recovered after methanol decomposition reaction exhibited IR absorption bands characteristics of olefinic species formed on Brønsted and Lewis acid sites. The IR spectra of coked samples recovered after phenol methylation showed the presence of phenolate, aromatic and polyaromatic species adsorbed mainly on Lewis acid sites.